Oral Administration of Nicotinamide Mononucleotide Is Safe and Efficiently Increases Blood Nicotinamide Adenine Dinucleotide Levels in Healthy Subjects - Okabe, Keisuke; Yaku, Keisuke; Uchida, Yoshiaki; Fukamizu, Yuichiro; Sato, Toshiya; Sakurai, Takanobu; Tobe, Kazuyuki; Nakagawa, Takashi (Frontiers in Nutrition, 2022)
Nicotinamide mononucleotide (NNM) is an orally bioavailable NAD+ precursor that has demonstrated beneficial effects against aging and aging-associated diseases in animal models. NMN is ultimately converted to NAD+, a redox cofactor that mediates many metabolic enzymes. NAD+ also serves as the substrate for poly(ADP-ribose) polymerase (PARP) and sirtuins, and regulates various biological processes, such as metabolism, DNA repair, gene expression, and stress responses. Previous mouse models showed that NMN administration can increase NAD+ in various organs and ameliorate aging-related diseases, such as obesity, diabetes, heart failure, stroke, kidney failure, and Alzheimer’s disease through NAD+-mediated pathways. However, evidence of its effect on humans is still scarce. In this study, we conducted a placebo-controlled, randomized, double blind, parallel-group trial to investigate the safety of orally administered NMN and its efficacy to increase NAD+ levels in thirty healthy subjects. Healthy volunteers received 250 mg/day of NMN (n=15) or placebo (n=15) for 12 weeks, and physiological and laboratory tests were performed during this period. In addition, NAD+ and its related metabolites in whole blood were examined. Oral supplementation of NMN for 12 weeks caused no abnormalities in physiological and laboratory tests, and no obvious adverse effects were observed. NAD+ levels in whole blood were significantly increased after NMN administration. We also observed the significant rise in nicotinic acid mononucleotide (NAMN) levels, but not in NMN. We also found that the increased amount of NAD+ was strongly correlated with pulse rate before the administration of NMN. These results suggest that oral administration of NMN is a safe and practical strategy to boost NAD+ levels in humans.